Three new species of the ant-mimetic plant bug genus Pilophorus from Japan (Hemiptera: Heteroptera: Miridae: Phylinae: Pilophorini) - Yasunaga, Tomohide; Duwal, Ram Keshari (Zootaxa, 2016)
Three new species of the ant-mimetic plant bug genus Pilophorus Hahn, P. maeharai, P. nakatanii and P. tagoi, are described from Japan, with information on their host associations. The genus is briefly diagnosed and discussed, including P. typicus (Distant) which is assumed to have two genotypes based on mitochondrial sequence data. The generic placement of P. tagoi, at first sight reminiscent of a certain member of Pherolepis Kulik, is also proven definitely. A checklist of all currently known species of Pilophorus in Japan is provided, with compiled distribution and host records.